The impact of ECB corporate sector purchases on European green bonds - Franziska Bremus; Franziska Schütze; Aleksandar Zaklan (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This papers analyzes the effect of the ECB's Corporate Sector Purchase Programme (CSPP) and the recent Pandemic Emergency Purchase Programme (PEPP) on the yields of eligible green bonds, a new but rapidly growing segment of the corporate bond market. We exploit these policy changes using a difference-in-differences strategy, with ineligible corporate green bonds issued in euro, U.S. dollars and Swedish crowns as comparison groups. We find that both programs significantly improve financing conditions for eligible green bonds, thereby increasing the attractiveness of these instruments to issuers and of the euro area as a location of issuance. The effects of the CSPP and PEPP are heterogeneous, both in terms of average impact and persistence of the effects. Yield differences between eligible and ineligible green bonds can last for more than six months. Our analysis informs the debate about new financing options for firms as well as about effects of asset purchase programs on the transition towards a less carbon-intensive economy.
Keywords: E52; E58; G12; G18; Q54; 330; green bonds; bond yields; monetary policy; corporate sector purchase programme(CSPP); pandemic emergency purchase programme (PEPP)